Homer: A Forerunner of Neoclassical Economics (2012)
Homer clearly expressed the economic problem of choosing the best option among several alternatives given a certain set of restrictions. In the Odyssey he specifically wrote about the minimum cost choice. This kind of problem, as is well known, is at the heart of the neoclassical economics. We can therefore consider Homer a forerunner of this school of thought. This hypothesis contrasts with those of Trever (1916), Schumpeter (1954) and Schefold (1997).